Political connections, corruption and tax evasion: a cross-country investigation. Issue 2 (1st April 2019) - Khlif, Hichem; Amara, Ines
Abstract : Purpose: This paper aims to examine the association between political connections and tax evasion and test whether corruption level affects this relationship. Design/methodology/approach: Tax evasion measure is based onSchneider et al. (2010 ), while country's political connection trend is based onFaccio (2006 ). Findings: Using a sample of 35 countries, the authors document that political connections are positively associated with tax evasion and this relationship becomes stronger for high corrupt environment. Originality/value: The findings have policy implications for countries aiming to combat tax evasion as political connection trends in one country reduce the level of tax compliance. In addition, political connections and corruption play a complimentary role in increasing tax evasion practices.